Pendayagunaan Keterampilan Motorik Peserta Didik Sekolah Dasar Melalui Pelatihan Membuat Bangku Belajar dari Barang Bekas - Maria Purnama Nduru; Siprianus See; Berty Sadipun; Finsensius Mbabho; Maria Finsensia Ansel (LPPM Universitas Flores, 2021)
Motoric skills are one of the human potential in this case learners are very important to be developed and empowered at all times along with the growth of humans themselves. To develop motor skills that are beneficial for learners, there needs to be a simple activity that is adjusted to the age and cognitive level of learners. Training to make benches learn from used goods to learners, actually aims to use motor skills and direct learners to do simple activities but have a very positive impact on the growth and development of learners themselves. This method of activity is a training that has several simple stages, ranging from providing explanations about the benefits of used goods and motor skills, learners are formed in groups in an organized manner, prepare materials and tools, then carry out tasks by utilizing tools and materials in making study benches. The result of this training activity is in the form of objects that are useful or have useful value, namely a simple learning bench in accordance with the creativity of learners and the achievement of the utilization of motor skills in a more useful direction for the learners themselves. Thus it can be concluded that the activities of this training can create enthusiasm in using the motor skills of learners early on, so that it can be one of the provisions for their survival.